Genotype‐dependent and heat‐induced grain chalkiness in rice correlates with the expression patterns of starch biosynthesis genes. Issue 4 (15th June 2021) - Gann, Peter James; Esguerra, Manuel; Counce, Paul Allen; Srivastava, Vibha
Abstract: Starch biosynthesis is a complex process underlying grain chalkiness in rice in a genotype‐dependent manner. Coordinated expression of starch biosynthesis genes is important for producing translucent rice grains, while disruption in this process leads to opaque or chalky grains. To better understand the dynamics of starch biosynthesis genes in grain chalkiness, six rice genotypes showing variable chalk levels were subjected to gene expression analysis during reproductive stages. In the chalky genotypes, peak expression of the large subunit genes of ADP‐glucose pyrophosphorylase ( AGPase ), encoding the first key step in starch biosynthesis, occurred in the stages before grain filling commenced, creating a gap with the upregulation of starch synthase genes, granule bound starch synthase I ( GBSSI ) and starch synthase IIA ( SSIIA ). Whereas, in low‐chalk genotypes, AGPase large subunit genes expressed at later stages, generally following the expression patterns of GBSSI and SSIIA . However, heat treatment altered the expression in a genotype‐dependent manner that was accompanied by transformed grain morphology and increased chalkiness. The suppression of AGPase subunit genes during early grain filling stages was observed in the chalky genotypes or upon heat treatment, which could result in a limited pool of ADP‐Glucose for synthesizing amylose and amylopectin, the major components of the starch. This suboptimal starch biosynthesis process could subsequently lead to inefficient grain filling and air pockets that contribute to chalkiness. In summary, this study suggests a mechanism of grain chalkiness based on the expression patterns of the starch biosynthesis genes in rice. Abstract :